2009
DOI: 10.1590/s1020-49892009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Lesiones de causa externa en menores y mayores de 18 años en un hospital colombiano

Abstract: The number of patients less than 18 years of age with injuries from external causes being treated at the Mario Correa Rengifo Hospital is constantly rising. The circumstances regarding injuries seen in children and adolescents differ from those of adults in that minors tend to suffer more unintentional injuries in the home or in the street where they play regularly. It is important that special educational and structural strategies be implemented to prevent injuries of this type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…Conversely, Latin America lacks reporting of emergency trauma visits, which are the most frequent events in the region 8 . The most similar report concerns the trauma registry completed from 2002 to 2004 in San Fernando General Hospital of Trinidad and Tobago 9 . In Colombia, strategies have been developed to monitor externally inflicted wounds from which the pertinent variables related to the history of these wounds can be cataloged 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Latin America lacks reporting of emergency trauma visits, which are the most frequent events in the region 8 . The most similar report concerns the trauma registry completed from 2002 to 2004 in San Fernando General Hospital of Trinidad and Tobago 9 . In Colombia, strategies have been developed to monitor externally inflicted wounds from which the pertinent variables related to the history of these wounds can be cataloged 10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is agreement on the fact that male patients (15-34 years) are more prone to suffer ECIs and that traffic accidents demand higher use of hospitalization services. 1,3,20 In this ECI group it was also found that it is common for patients to be referred by a state health services unit and to require pre-hospital care, which can be indicative of the severity of injuries. The characteristics shown by the cluster analysis include the anatomical regions involved, place of occurrence, destination after care and patients' age and gender, among others.…”
Section: Discussionmentioning
confidence: 98%
“…The groups formed using this tool can be appreciated to be similar to those proposed by Ávila-Burgos et al 1 and that the results are consistent with those reported in other studies. [1][2][3]19,20 This type of techniques provide additional information on the structure of the groups and the behavior of included variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations